The role of laparoscopic surgery in current treatment of endometriosis (Medical Journal of Indonesia, 2006)
The objective of this paper is to discuss the current guidelines for treatment of endometriosis, emphasis on the role of laparoscopic surgery and medical treatment. The accuracy of diagnosis of endometriosis without laparoscopy is very low, as a false negative rate of 19 % and a false positive rate of 44%, when a diagnosis was made pre laparoscopy, 81% had the diagnosis can confirmed on laparoscopy, while 19% did not have endometriosis. It is concluded that laparoscopy is required for evaluation and treatment of endometriosis. Medical therapy is effective in reducing progression of endometriosis score. (Med J Indones 2006; 15:121-4)